Peningkatan Hasil Belajar Berbasis Proyek Untuk Meningkatkan Keterampilan Menggunakan Arduino - Priyulida, Fitria; Harold Situmorang; Syahputri Maharani (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
To increase the potential of students' skills, innovative and creative and technology-based learning is needed, because differences in personal background, understanding and interests often make students feel less enthusiastic about learning, one of the innovative learning is learning with a project-based approach because this project approach can be a solution to improve students' abilities and skills in understanding the material which is conveyed while remaining student-centered.